The Epstein-Barr Virus Enhancer Interaction Landscapes in Virus-Associated Cancer Cell Lines - Ding, Weiyue; Wang, Chong; Narita, Yohei; Wang, Hongbo; Leong, Merrin Man Long; Huang, Alvin; Liao, Yifei; Liu, Xuefeng; Okuno, Yusuke; Kimura, Hiroshi; Gewurz, Benjamin; Teng, Mingxian; et al. (Journal of virology, 2022)
EBV is the first human DNA tumor virus identified, discovered over 50 years ago. EBV causes ~200,000 cases of various cancers each year. Epstein-Barr virus (EBV) persists in human cells as episomes. EBV episomes are chromatinized and their 3D conformation varies greatly in cells expressing different latency genes. We used HiChIP, an assay which combines genome-wide chromatin conformation capture followed by deep sequencing (Hi-C) and chromatin immunoprecipitation (ChIP), to interrogate the EBV episome 3D conformation in different cancer cell lines. In an EBV-transformed lymphoblastoid cell line (LCL) GM12878 expressing type III EBV latency genes, abundant genomic interactions were identified by H3K27ac HiChIP. A strong enhancer was located near the BILF2 gene and looped to multiple genes around BALFs loci. Perturbation of the BILF2 enhancer by CRISPR interference (CRISPRi) and CRISPR activation (CRISPRa) altered the expression of BILF2 enhancer-linked genes, including BARF0 and BALF2, suggesting that this enhancer regulates the expression of linked genes. H3K27ac ChIP followed by deep sequencing (ChIP-seq) identified several strong EBV enhancers in T/NK (natural killer) lymphoma cells that express type II EBV latency genes. Extensive intragenomic interactions were also found which linked enhancers to target genes. A strong enhancer at BILF2 also looped to the BALF loci. CRISPRi also validated the functional connection between BILF2 enhancer and BARF1 gene. In contrast, H3K27ac HiChIP found significantly fewer intragenomic interactions in type I EBV latency gene-expressing primary effusion lymphoma (PEL) cell lines. These data provided new insight into the regulation of EBV latency gene expression in different EBV-associated tumors. IMPORTANCE EBV is the first human DNA tumor virus identified, discovered over 50 years ago. EBV causes ~200,000 cases of various cancers each year. EBV-encoded oncogenes, noncoding RNAs, and microRNAs (miRNAs) can promote cell growth and survival and suppress senescence. Regulation of EBV gene expression is very complex. The viral C promoter regulates the expression of all EBV nuclear antigens (EBNAs), some of which are very far away from the C promoter. Another way by which the virus activates remote gene expression is through DNA looping. In this study, we describe the viral genome looping patterns in various EBV-associated cancer cell lines and identify important EBV enhancers in these cells. This study also identified novel opportunities to perturb and eventually control EBV gene expression in these cancer cells.